2002
DOI: 10.1017/s0021859602002289
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spray application of urea fertilizer at stem extension on winter wheat: N recovery and nitrate leaching

Abstract: A field experiment was carried out at Harper Adams in Shropshire to investigate the effect of supplying the spring N application to winter wheat as different proportions of urea as a solution, rather than as conventional soil-applied solid urea, on N recovery in the above-ground crop, autumn soil mineral N and nitrate leaching over the subsequent winter. A solid ammonium nitrate treatment was also included to represent alternative commercial practice to solid urea. Treatments were repeated on the same plots ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
5
0
1
Order By: Relevance
“…As a result, nitrogen fertilizers of different chemical composition may have various effects on nitrogen leaching and environmental pollution. Experiments performed in England showed that under different climatic conditions nitrogen uptake and leaching from liquid and granular urea and ammonium nitrate varied (Readman et al, 2002). In one year, plants assimilated more nitrogen from liquid fertilizer, the next year no differences were observed.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, nitrogen fertilizers of different chemical composition may have various effects on nitrogen leaching and environmental pollution. Experiments performed in England showed that under different climatic conditions nitrogen uptake and leaching from liquid and granular urea and ammonium nitrate varied (Readman et al, 2002). In one year, plants assimilated more nitrogen from liquid fertilizer, the next year no differences were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al (1991) observed positive increases in GPC with foliar N application, and greater increase in GPC was obtained when the application was made close to flowering. However, Readman et al (2002) reported no additional yield advantage of foliar‐sprayed urea as compared to the soil applied fertilizer. Woolfolk et al (2002) concluded that late season foliar N applications before or immediately after flowering may significantly enhance GPC in winter wheat.…”
mentioning
confidence: 96%
“…The recovery of foliar‐applied N at the later stages of wheat development has been assessed using Isotopic 15 N labeling (Powlson et al, 1989; Smith et al, 1991; Rawluk et al, 2000; Readman et al, 2002). Powlson et al (1989) at Rothamsted, UK reported a recovery of about 70% of the foliar‐applied N given at anthesis in the aboveground parts, including 64% in grains.…”
mentioning
confidence: 99%
“…Using a 15 N-labeling technique can help determine the recovery of foliar-applied N in wheat (Triticum aestivum L.) (Powlson et al 1989;Smith et al 1991;Rawluk et al 2002). Powlson et al (1989) reported that the recovery could be up to 70% through foliar application of N at anthesis in the aboveground parts including 64% in grains, whereas Rawluk et al (2000) recently reported that the recovery of foliar-applied N in wheat grain was much lower (5.5 to 26.7%) than that of soil-applied N (32.3 to 70.1%), and grain yield and protein were also higher for soil-applied than for foliar-applied N. Similarly, Readman et al (2002) observed a lower recovery of foliar-applied N than in the soil-applied treatment. Smith et al (1991) observed that grain N concentration increased with foliar N application and a greater increase in grain protein occurred when the application was close to flowering.…”
mentioning
confidence: 98%